Impact of Nathpa Jhakri Hydroelectric Power Project on Production and Productivity of Livestock in Kinnaur and Shimla Districts of Himachal Pradesh - Katoch, Anup; Guleria, Jagtar; Kumar, Ashok (Indian Journal of Extension Education, 2018)
Nathpa Jhakri Power Project is the biggest hydro-electric project of the country built on the Satluj river and is located in  Shimla and Kinnaur districts of Himachal Pradesh. Although, hydroelectric projects offer opportunities for infrastructure  development and economic growth; but if not well designed, implemented and operated, they have the potential to  adversely affect the communities. In this study an attempt has been made to study the pros and cons of the power project on  production and productivity of livestock. By studying the sample of 200 random selected families. It is concluded that  Nathpa Jhakri hydroelectric power project has positive impact on the production and productivity livestock in the  surrounding panchayats.
Keywords: Hydroelectric; livestock; power; production; productivity